Factors influencing value addition to cashew products processed in the South-East Zone, Nigeria: A multinomial logistic regression approach - Anayochukwu Victor EZE; Ibrahim Macharia; Lucy Ngare (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2022)
Nigeria is a leading cashew producer, but this has not been reflected in the development of the downstream cashew value chain industry. The launch of the "Agriculture Promotion Policy (2016 - 2020)" document was designed to encourage value addition to export crops such as cashew as ways of creating jobs and wealth to value chain actors. However, it is still unclear why cashew processors are unable to exploit this opportunity to improve value addition to cashew. This makes it imperative that factors influencing value addition to cashew products in the South-East zone, Nigeria be analyzed. A cross-sectional survey design involving a structured questionnaire was used to obtain data from 353 randomly selected respondents from the South-East zone, Nigeria. The study found that income, access to market, product characteristics, and cost of cashew processing technology significantly influence value addition to cashew products in the two models, whereas government policy on cashew processing and market facilities were significant in the second model. The relative risk ratios for age, educational level, income, processing experience, access to market, distance to market, government policy on cashew processing and market facilities were > 1, suggesting the likelihood of processor's preferring to add value to cashew kernel, and both cashew products as against cashew nut for any unit increase in these variables. This study provided vital insights about how the relative significance of these factors will aid policy analysts and decision-makers to determine which of the factors to focus on while developing specific policies for the cashew value chain industry.